2020
DOI: 10.3390/educsci10030049
|View full text |Cite
|
Sign up to set email alerts
|

Readiness, Roles, and Responsibilities of Stakeholders for Sustainable Mobile Learning Adoption in Higher Education

Abstract: The extant literature on mobile learning in higher education has mainly focused on students and academics. This study conducted in a Nigerian university considered a wider group of stakeholders (students, academics, IT personnel, and administrative leaders) in its investigation of stakeholders’ awareness, willingness, and readiness for mobile learning adoption, using a mixed methods approach. The findings revealed that while the awareness of mobile learning amongst students was low, they were keen on adoption.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 48 publications
2
14
0
1
Order By: Relevance
“…Ibrahim and Nat (2019) argue that the operating system of e-learning platforms, blended classrooms and related electronic materials design must incorporate usability elements as a fundamental factor in establishing a distance learning environment. Original research found that the online interaction and system usability by students and educators within a particular HEI notably impact their engagement in terms of cognitive, behavioral, emotional and agentic engagement (Bai, 2019;Chavoshi and Hamidi, 2019;Crompton and Burke, 2018;Okai-Ugbaje et al, 2020;Pimmer et al, 2016).…”
Section: System Usabilitymentioning
confidence: 99%
“…Ibrahim and Nat (2019) argue that the operating system of e-learning platforms, blended classrooms and related electronic materials design must incorporate usability elements as a fundamental factor in establishing a distance learning environment. Original research found that the online interaction and system usability by students and educators within a particular HEI notably impact their engagement in terms of cognitive, behavioral, emotional and agentic engagement (Bai, 2019;Chavoshi and Hamidi, 2019;Crompton and Burke, 2018;Okai-Ugbaje et al, 2020;Pimmer et al, 2016).…”
Section: System Usabilitymentioning
confidence: 99%
“…In addition, personal innovation and previous experiences in mobile social media directly influence student use in the university environment (SIDIK; SYAFAR, 2020). It is noteworthy that in depressed socioeconomic and cultural contexts, knowledge about the m-learning process is low, although there is a lot of interest in its use (OKAI-UGBAJE et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…El uso de M-Learning es una tendencia a nivel mundial, pese a que en países desarrollados se legitima por parte de los estudiantes, en países en vía de desarrollo las instituciones hacen importantes esfuerzos por estar a la vanguardia y reducir la brecha digital, en diversos niveles como la educación superior [36,73], primaria y secundaria [74]. Al respecto Colombia a través de programas como "Colombia vive digital" ha masificado el desarrollo de infraestructura orientada a dar conexión a Internet y facilitar el acceso a dispositivos móviles, principalmente tabletas.…”
Section: Discussionunclassified